Higher Education in Africa: A Complex but Hardly Researched Enterprise - Zavale, Nelson (International Higher Education, 2022)
As elsewhere, higher education (HE) in Africa has become a complex enterprise, yet is hardly researched. This article presents the main findings of a systematic review of literature focusing on African HE and published from 1980 to 2019, and suggests that the transformation of African HE was not accompanied by an equivalent production of research focusing on it, which is crucial to make its features and developments intelligible and guide policy makers and practitioners.